2022
DOI: 10.1002/sim.9332
|View full text |Cite
|
Sign up to set email alerts
|

Common scale minimal sufficient balance: An improved method for covariate‐adaptive randomization based on the Wilcoxon‐Mann‐Whitney odds ratio statistic

Abstract: Minimal sufficient balance (MSB) is a recently suggested method for adaptively controlling covariate imbalance in randomized controlled trials in a manner which reduces the impact on randomness of allocation over other approaches by only intervening when the imbalance is sufficiently significant. Despite its improvements, the approach is unable to consider the relative clinical importance or magnitude of imbalance in each covariate weight, and ignores any imbalance which is not statistically significant, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The newly proposed CSSize-MSB algorithm will incorporate a measure of group size balance control into the existing CS-MSB algorithm. CSSize-MSB uses the previously demonstrated mechanisms of CS-MSB 22 to estimate covariate imbalance with the generalized odds ratio. 25 Additionally, CSSize-MSB will estimate the group size imbalance between the treatment groups after each individual patient randomization as the proportion of allocated patients that have been randomized to the control group.…”
Section: Incorporating Group Size Balance Into the Cs-msb Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…The newly proposed CSSize-MSB algorithm will incorporate a measure of group size balance control into the existing CS-MSB algorithm. CSSize-MSB uses the previously demonstrated mechanisms of CS-MSB 22 to estimate covariate imbalance with the generalized odds ratio. 25 Additionally, CSSize-MSB will estimate the group size imbalance between the treatment groups after each individual patient randomization as the proportion of allocated patients that have been randomized to the control group.…”
Section: Incorporating Group Size Balance Into the Cs-msb Algorithmmentioning
confidence: 99%
“…2 This type of randomization approach has not only been used in stroke research but also in Parkinson disease 20 and COVID-19 research. 21 An extension of this randomization method called common-scale minimal sufficient balance (CS-MSB) 22 has been proposed that provides improved covariate balance with the same level of treatment allocation randomness compared with MSB. Additionally, it has been demonstrated that CS-MSB has identical type 1 error and power control compared with MSB.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this trial, the two-arm, two-stage design was complemented by an adaptive sample size reestimation within the second stage using the Mehta and Pocock method described above 30 . The randomisation for this trial uses the covariate adaptive common scale minimum sufficient balance algorithm 38 that improves the balance of key prognostic variables while maximizing the randomness of allocation.…”
Section: Introductionmentioning
confidence: 99%